Pengembangan Program Tahfidz Al-Qur'an sebagai Strategi Keunggulan Lembaga Pendidikan Nonformal - Imam Rohhani; Zaki Ulien Nuha; Moch. Danu Kurniadi (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to analyze the development of the Qur'anic memorization (tahfidz Al-Qur'an) program and explain its role in fostering the institutional excellence of PKBM Ibadurrahman Sidoarjo. Previous studies on tahfidz programs have primarily focused on learning processes, program management, and students’ memorization achievements, while studies examining tahfidz as a strategy for developing institutional excellence, particularly in non-formal educational institutions such as Community Learning Activity Centers (PKBM), remain limited. This study employed a qualitative approach with a case study design. Data were collected through in-depth interviews and document analysis and analyzed using the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing. The findings reveal that the development of the tahfidz program is carried out through positioning tahfidz as an institutional flagship program, strengthening human resource competencies, and developing a quality assurance system. Furthermore, the program serves as the institution’s identity and distinguishing characteristic, enhances educational quality and public trust, and improves graduates’ quality and competitiveness. These findings imply that the tahfidz Al-Qur'an program functions not only as a religious learning program but also as a strategic instrument for building excellence in non-formal educational institutions